Catch The Different Octopus(Octopus Vulgaris) With Shell Mussels And Material Cement In The Village Kuala Tanjung Indah Batubara District Regency Of North Sumatera - Jefri granico; Arthur Brown; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted on august 2016 in Kuala Tanjung Indah village Batubara Regency of Riau. This research aims to compare the catch octopus use two different types of cement and native shellfish shell as control. The method use in this research is a survey conducted for 10 days. The catches during of research were 25,44kg (248 fishes). The result of research for shell is 8,85kg (86 fishes), for cup is 9,15kg(89 fishes), and for round is7,43kg (73 fishes). Most catch level low of a bowl shape and spherical shape.Keyword: Differences in catch, Kuala Tanjung Indah village, Octopus